Professional expectations of students of the oral health technician course - José Ferreira Lima Junior; Lívia Lopes Fonteles Serrano Dantas; Caroline Antero Machado; Maria Elisa Machado Ferreira Marcelo (Universidade de Fortaleza, 2012)
Objective: To identify the expectations of students enrolled in the oral health technician course conducted by the School of Public Health of Ceará, about their professional future. Methods:This work presents a quantitative, cross-sectional descriptive study held with students of seven classes in dental hygiene course conducted by the School of Public Health. Data collection was conducted between March and April 2011, through the application of a semistructured questionnaire, which addressed the professional profile of the participants, their expectations about the labor market and the profession. Statistical analysis was performedwith a degree of significance of 0.05. Results: 154 students were interviewed, of whom 96.1% were women, mean age of 32.9 (± 7.3) years. Most (93.8%, N = 120) graduated from high school and 71.1% (N = 108) were registered at the Regional Council of Dentistry. Regardingtheir insertion in the labor market, 42.9% believed it would be satisfactory and 58% that it would occur in public service. The biggest obstacle mentioned by the subjects about the insertion of oral health technicians in the labor market was the difficulty of hiring (45.5%). When asked to punctuate some actions that they would play as TSB, 82.2% cited clinical and collective actions. The majority (96%) claimed to feel safe to act as TSB. Conclusion:The students' expectations regarding their professional future are positive. However, it is necessary to develop further research in this area, so that the profession has a growing support within the labor market.